Full-stack web development for auto-assessment platform - Cholakov Kristiyan Kamenov (Nanyang Technological University, 2024)
This project highlights the limitations of the existing digital evaluation system and identifies the lack of a complete self-sustained platform for conducting comprehensive handwritten examinations on a digital platform that does not involve the usage of external software or hardware tools. The paper presents a novel end-to-end architecture that stands out from the competitors with its ability to integrate every stage of the examination, while previous approaches provide partial solutions that aim to speed only parts of the whole process. The project represents the first platform with its own exam management console, handwritten input capturing, image-to-text recognition for pages with handwritten content, and LLM-based grading assistant.